Mantenimiento a banco de instrumentación industrial para la medición de temperatura y presión del Laboratorio de Automatización y Control de la Facultad de Ingeniería Mecánica, Eléctrica y Biomédica de la Universidad Antonio Nariño sede Cartagena (2023)
This project abaut Maintenance of an industrial instrumentation bench for measuring temperature and pressure was developed at the Antonio Nariño University Cartagena headquarters Nariño, as graduation project of the Industrial Electromechanical Maintenance Technology, where the knowledge acquired during the development of the classes was applied, managing to methodologically develop a series of maintenance activities such as: problem diagnosis, application of corrective maintenance, implementation of preventive maintenance, getting that it was possible to restore the functionality of each of the modules that are part of this project, which allows it to continue being used by the students of the Faculty of Mechanical, Electrical and Biomedical Engineering from the headquarters.